Aging and degeneration of the intervertebral disc: review of basic science - Josemberg da Silva Baptista; Ricardo Bragança de Vasconcellos Fontes; Edson Aparecido Liberti (Coluna/Columna, 2015)
Currently there is a growing interest in the study of intervertebral discs due to loss of manpower brought to society by low back and neck pains. These papers seek to delineate the difference between normal aging and disc degeneration, trying to understand what factor would be determining for the second condition. Thus, the morphology field was expanded and knowledge on the structure of intervertebral discs currently uses the research field of cell and molecular biology, and genetics. The results indicate that regardless of age or condition, the intervertebral disc undergoes long and extensive remodeling of its constituents, which are influenced by several factors: environmental, soluble, cell growth and extracellular matrix. In this literature review we describe the biological characteristics of the cervical and lumbar intervertebral disc with a focus on basic science of aging and degeneration, selecting the latest findings and discussions of the area, which influence future research and clinical thoughts.